The damage of the Watson–Crick base pairs by nickel nanoparticles: A first-principles molecular dynamics study. (August 2020) - Martínez-Zapata, Daniel; Santamaria, Ruben
Graphical abstract: Highlights: Nickel nanoparticles (Ni2 and Ni3 ) are harmful atmospheric pollutants which damage humans. Quantum molecular simulations for the molecular system under realistic thermodynamic conditions (NVT) are performed. The results show the formation of stable organometallic compounds of the Ni nanoparticles with the DNA nucleic acid bases. The organometallic compounds may be a factor in the development of diseases for the people exposed to the Ni nanoparticles. Abstract: The nickel nanoparticles are harmful atmospheric pollutants, and the damage caused by them in humans has become a topic of great relevance. In this study we investigate the interaction of the Ni2 and Ni3 clusters with the AT and GC Watson–Crick base pairs in an aqueous medium. Molecular dynamics in combination with density functional theory are employed. A novel method is implemented to create realistic thermodynamic conditions (NVT) in the simulations. The energies, the charges of the interacting compounds, the temperature changes, and the geometric rearrangements are reported. The results show the formation of stable organometallic compounds of the nickel nanoparticles with the DNA nucleic acid bases. In this respect, the biological processes where the DNA is implicated may be altered by the formation of such super-structures.